On the Tax Fraud as criminal activity precedent of the Money Laundering (2016)
Does the tax offense constitute prior criminal activity for the purposes of money laundering offense committed by the active same subject? From one side, both the current regulation of article 301 of the Spanish Criminal Code (which explicitly acknowledge